Dietary Diversity and Its Associations with Anemia among Women of Reproductive Age in Rural Odisha, India. Issue 3 (4th May 2022) - Jin, Yichen; Talegawkar, Sameera A.; Sedlander, Erica; DiPietro, Loretta; Parida, Manoj; Ganjoo, Rohini; Aluc, Aika; Rimal, Rajiv
ABSTRACT: The aim of this study is to examine diet diversity, predictors associated with it, and its associations with anemia among non-pregnant women of reproductive age in rural India. Baseline data from the Reductions in Anemia through Normative Innovations (RANI) project were used and included 980 non-pregnant women aged 15–49 years from Odisha, India. The Food and Agriculture Organization's Minimum Dietary Diversity for Women (MDD-W) was used to assess diet diversity. Anemia was determined by hemoglobin level and categorized as normal (hemoglobin ≥ 12 g/dL), mild (11 ≤ hemoglobin <12 g/dL) and moderate/severe (hemoglobin < 11 g/dL). Multivariable logistic regression was used to examine factors associated with diet diversity, and multinomial logistic regression for associations between diet diversity and anemia. Forty-four percent of women were classified as having a diverse diet (MDD-W ≥5). Women with higher education level, belonging to a scheduled caste (vs. tribe), and higher body mass index had higher odds of a diversified diet ( p < .05 for all). A more diverse diet was associated with 30% of lower odds of mild anemia (odds ratio = 0.7, 95% confidence interval: 0.5–0.98, p = .035), however, no statistically significant associations were found for moderate/severe anemia. Diet diversity was inversely associated with prevalence of mild anemia among non-pregnant women of reproductive age in rural India.